Prevalence and risk factors of obesity among higher secondary school students in urban and rural schools of North Kerala - K. V., Urmila; Krishnan K., Divya; Sudakaran, .; Nambiar, Muralikrishnan (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood overweight and obesity have become an important public health problem. Life style approach is required, and requires political and social commitment in addition to medical management. We investigated the prevalence of obesity and the association with risk factors relating to physical activities, in higher secondary school children of government and private schools. Methods: In 2015, we surveyed higher secondary students in North Kerala both in government and private sector schools. We measured height, weight and plotted Body mass Index on CDC (Child Developement Centre) charts. Factors affecting obesity like physical and sedentary activities (using Bharathy et al questionnaire) and school-based risk factors were also studied. Results: Multivariate logistic regression was done to evaluate the significance of these risk factors for overweight and obesity. On the basis of measurements taken in 496 higher secondary school students, the estimated provincial prevalence of overweight was found to be 7%, obesity 3% and malnutrition 18%. Children who studied in private school was found to have increased risk of overweight p=0.02 with odds ratio (OR of 2.97 95% confidence interval CI 1.27-6.97), whereas those who went to school by walking were at decreased risk (OR 2.78, 95% CI 1.16-6.65). Students involved in house hold chores for 4hours or more a week were associated with a decreased risk of overweight (OR 3.96, 95% CI 1.42-11.07) and those with less activity were at increased risk for obesity (OR 6.61, 95% CI 1.91-22.84). Conclusions: Home and schools provide important opportunities for public health initiatives for reducing childhood overweight and obesity. Children in private schools coming from higher socio-economic background are being less physically active and has thus susceptible to obesity and its consequences.